Strategy to Increase Sales through Rebranding and Diversification of Ginger Syrup "Dwi Dewii" - Muchlisiniyati Safeyah; Virginia Mandasari; Ramadhani Mahendra Kusuma (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2024)
This article examines the strategy to increase the sales of "Dwi Dewii" ginger syrup in Kelurahan Bendo through rebranding and product diversification. Ginger syrup, known for its health benefits such as boosting immunity, faces challenges in marketing and sales, primarily due to conventional marketing strategies that only target adult consumers and are less appealing to younger audiences. This program aims to identify the gaps in current marketing strategies and develop new methods to enhance the product’s appeal and sales. The methodology used includes observation, interviews, and an analysis of existing packaging designs and marketing techniques. This community service project involved four lecturers and three students, collaborating with the primary partner, "Dwi Dewii" Ginger Syrup small-scale enterprise, and four other local small-scale enterprises producing traditional Blitar souvenirs in Kelurahan Bendo. The steps taken included redesigning the product packaging, providing training in digital marketing, and product diversification. Rebranding and diversification are expected to increase market appeal and broaden the consumer base, especially among younger demographics. The new packaging design aims to enhance the product's quality perception and attract a wider range of consumers. Product diversification is anticipated to improve customer satisfaction and boost sales volume. Furthermore, optimizing digital marketing through social media and e-commerce has proven effective in increasing visibility and consumer interaction, ultimately contributing to the economic growth of the partner small-scale enterprises.Artikel ini mengkaji strategi peningkatan penjualan produk sirup jahe "Dwi Dewii" di Kelurahan Bendo melalui pendekatan rebranding dan diversifikasi produk. Sirup jahe yang dikenal karena manfaat kesehatannya, seperti meningkatkan imunitas, menghadapi tantangan dalam hal pemasaran dan penjualan. Hal ini terutama disebabkan oleh strategi pemasaran konvensional yang hanya menjangkau kalangan usia dewasa dan kurang menarik bagi konsumen usia remaja. Program ini bertujuan untuk mengidentifikasi permasalahan dalam strategi pemasaran yang ada serta mengembangkan metode baru yang dapat meningkatkan daya tarik dan penjualan produk. Metode yang digunakan meliputi observasi, wawancara, dan analisis terhadap desain kemasan serta teknik pemasaran yang sedang diterapkan. Kegiatan pengabdian ini melibatkan empat dosen dan tiga mahasiswa, yang bekerja sama dengan mitra utama, yaitu UMKM Sirup Jahe Merah "Dwi Dewii", serta empat UMKM lainnya yang memproduksi oleh-oleh khas Kota Blitar di Kelurahan Bendo. Langkah-langkah yang dilakukan mencakup perancangan ulang kemasan produk, pelatihan pemasaran digital, dan diversifikasi produk. Rebranding dan diversifikasi diharapkan mampu meningkatkan daya tarik pasar serta memperluas segmentasi konsumen, termasuk kalangan remaja. Desain kemasan baru dirancang untuk memperbaiki citra kualitas produk dan menarik perhatian konsumen yang lebih luas. Diversifikasi produk diharapkan dapat meningkatkan kepuasan pelanggan dan volume penjualan. Selain itu, optimalisasi pemasaran digital melalui media sosial dan e-commerce dinilai efektif dalam meningkatkan visibilitas dan interaksi dengan konsumen, yang pada akhirnya berkontribusi pada pertumbuhan ekonomi mitra UMKM.